Construct a Strategy Combines Two Strategies Based on the Constructivist Principles and Measure its Effect on Acquisition of Environmental Concepts Among Ninth Basic Grade Students and Development of their Attitudes Towards Environment - Al-Alaween, Fareed; Al- Ayasrah, Ahmad (Jordan Journal of Educational Sciences, 2016)
This study aimed to construct a strategy that combines (POE) and (KWL) strategies which are based on the principles of constructivist theory—called the built-in strategy (PK, OW, EL); this study also investigated the effect of this strategy on acquisition of environmental concepts among ninth grade students and improving their attitudes towards environment. The members of the study were (99) students from Husni Fariz Basic School for Boys and Aisha bint Abu Bakr Mixed School in Al-Balqa Directorate of Education, in the academic year 2013/2014. The study was divided into experimental and control groups. Environmental concepts test consisting of (30) multiple-choice items, and a scale of attitudes towards environment consisting of (34) items were used. The results showed that the presence of statistically significant effect of the built-in strategy at (α=0.05) on the acquisition of environmental concepts and improving attitudes towards environment. Also, it showed that there was a statistically significant effect of the interaction between the built-in strategy and sex in improving attitudes towards environment, yet there was no statistically significant effect of the interaction between the built-in strategy and sex in acquisition of environmental concepts